2003
DOI: 10.2466/pms.2003.97.3.960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teaching with Mirrors on Ballet Dance Performance

Abstract: This study assessed the effect of mirrors on the dance performance of beginning college ballet students in the classroom setting, using an evaluation methodology developed for this study. 13 women enrolled in one ballet class were taught using mirrors, 14 women in a second beginning ballet class were taught without mirrors. Both classes were taught by the same instructor. All students were videotaped performing the same adagio and grand allegro phrase during Weeks 5 and 14 of the 14-wk. term. At the end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Radell et al [17] suggest that the use of the mirror in a ballet classroom may negatively affect the skill acquisition of a dancer. Some years later, the same authors concluded that while the use of a mirror has some benefits in training, higher performing dancers feel better about their body image when they do not use a mirror [18].…”
Section: Introductionmentioning
confidence: 99%
“…Radell et al [17] suggest that the use of the mirror in a ballet classroom may negatively affect the skill acquisition of a dancer. Some years later, the same authors concluded that while the use of a mirror has some benefits in training, higher performing dancers feel better about their body image when they do not use a mirror [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Radell et al [12] have suggested that the use of a mirror in a ballet classroom may negatively affect the skill acquisition of the dancer and ultimately impact their performance, which has contradicted the results from Dearborn et al [3]. The first study [12] has concluded that while 85.7 % of dancers remarked that the use of mirrors has influenced their understanding of the concepts taught, satisfaction with overall appearance decreased for high performing dancers in a mirrored class [11].…”
Section: Related Workmentioning
confidence: 99%
“…Studies by Radell et al [12] have suggested that the use of a mirror in a ballet classroom may negatively affect the skill acquisition of the dancer and ultimately impact their performance, which has contradicted the results from Dearborn et al [3]. The first study [12] has concluded that while 85.7 % of dancers remarked that the use of mirrors has influenced their understanding of the concepts taught, satisfaction with overall appearance decreased for high performing dancers in a mirrored class [11]. Green has expressed, in a critique of traditional dance instruction, "the constant focus on an externalized view of the body, as reflected in the mirror, objectifies the dancer's body and requires students to strive to achieve a specific 'look' while being 'corrected' so the students perform 'proper' dance technique" [7].…”
Section: Related Workmentioning
confidence: 99%
“…The mirrorwhich significantly affects classical ballet dancers -projects a one-dimensional reflection of the superficial body shape. However, at the very moment of reflection, the attitudes, judgements and criticisms of the subject regarding such an image also take place (Radell, Adame and Cole 2002;Radell, Adame, and Cole 2003;Radell, Adame and Steven 2004). There is a particular representation of the 'ideal' body (which either exists or needs to be formed) prevailing among professional dancers (Bronhorst et al 2001;Helen 1995;Tiggemann 2001).…”
Section: Literature Reviewmentioning
confidence: 99%